HEAT island studies at Delhi - BAHL , H. D.; PADMANABHAMURTY, B. (MAUSAM, 1979)
Mobile temperature surveys were conducted in Delhi during the winter months in the early hours m of 18 December 1976,29 Jauary1977, 26 February 1977 and 26 March1977. The surveys show the formation of heat island within the thickly populated walled city encompassing areas from Delhi Gate, Chandni Chowk to Ajmeri Gate. Secondary, Heat Island in the trans-Yamuna area and near Y usaf Sarai area in South Delhi are also found. The maximum temperature difference between the warmest part of the city and the coldest area of the suburb was nearly 5°C during December which increased to nearly 7°C in the months January to March.